Wartości prorodzinne w świadomości maturzystów puławskich (1994-2009-2016) - Mariański, Janusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article will discuss the key issues related to the place and role of family values in the hierarchy of modern values (family as a general value), marriage and partnership, methods and techniques of education inthe family and attitudes of young people towards Catholic norms ofmarital and family morality. These issues will be discussed in the lightof sociological research carried out in Puławy among secondary-school graduates in the years 1994-2009-2016. Although the families as a value is highly valued in Poland, at thesame time far-reaching changes have taken place in our country in terms of its structure, function, role division, power, transmission of values and norms. The most significant changes can be seen in the area ofsexual morality. Morality fostered by the Church’s ethical system is implemented in the life of a clear minority of the surveyed graduates, and even reaches the so-called critical state in some matters. The situation of essential, almost fundamental uncertainty as well as ambivalence that grows to the rank of a principle organizing moral life,indicates the emergence of something that could be described as postmodern morality.